2016
DOI: 10.1161/res.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Reactive Oxygen Species, Reactive Nitrogen Species, and Redox-Dependent Signaling in the Cardiovascular System

Abstract: Reactive oxygen species and reactive nitrogen species are biological molecules that play important roles in cardiovascular physiology and contribute to disease initiation, progression, and severity. Because of their ephemeral nature and rapid reactivity, these species are difficult to measure directly with high accuracy and precision. In this statement, we review current methods for measuring these species and the secondary products they generate and suggest approaches for measuring redox status, oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
258
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(270 citation statements)
references
References 384 publications
(442 reference statements)
9
258
1
2
Order By: Relevance
“…TRPC3 knockdown suppressed this cardiomyocyte atrophy ( Figure 3A) and increased 2',7'-dichlorofluorescein diacetate (DCFH 2 DA) fluorescence intensity ( Figure 3B). Despite the high sensitivity of DCFH 2 DA to ROS, this probe is limited to use for measuring intracellular ROS (31). Therefore, we used a genetically encoded fluorescent sensor for hydrogen peroxide, Hyper, and confirmed that a DOX-induced increase in Hyper fluorescence intensity was suppressed by the treatment with siRNA for TRPC3 or Nox2 in H9c2 cardiac myoblasts (Supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 75%
“…TRPC3 knockdown suppressed this cardiomyocyte atrophy ( Figure 3A) and increased 2',7'-dichlorofluorescein diacetate (DCFH 2 DA) fluorescence intensity ( Figure 3B). Despite the high sensitivity of DCFH 2 DA to ROS, this probe is limited to use for measuring intracellular ROS (31). Therefore, we used a genetically encoded fluorescent sensor for hydrogen peroxide, Hyper, and confirmed that a DOX-induced increase in Hyper fluorescence intensity was suppressed by the treatment with siRNA for TRPC3 or Nox2 in H9c2 cardiac myoblasts (Supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 75%
“…Interestingly, the reduction in hydrogen peroxide in vessels from hyperlipidemic females was associated with increased ROS generation evaluated by DHE fluorescence. DHE is widely used to detect superoxide generation with high sensitivity, although other oxidants can produce a 2‐electron oxidation product with similar fluorescence characteristics 50. Consequently, the results suggest increased superoxide generation concomitant with reduced hydrogen peroxide in small arteries of female hyperlipidemic mice.…”
Section: Discussionmentioning
confidence: 91%
“…From the confocal images, it can be seen that nuclei and/or mitochondria were labeled by DHE or Mito-SOX. However, due to the probes' DNA affinity and required higher resolution, precise ROS locations cannot be identified correctly in images [24]. Flow cytometry values had the least variation between repetitions among the three methods.…”
Section: Discussionmentioning
confidence: 97%
“…The main devices for fluorescence detection are flow cytometer, confocal microscopy and microplate reader, with respective advantages and disadvantages [24]. Flow cytometry is the most popular and sensitive method currently, but necessary steps such as digestion may influence ROS detection.…”
Section: Discussionmentioning
confidence: 99%